Implementasi Kurikulum Berbasis Karakter Dalam Meningkatkan Akhlakul Karimah di MTs Al-Amin Dompu - Syatriadin Syatriadin (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2019)
Talking about characters must have many references. Character as student personality can determine moral quality and behavior for students including in making decision. Therefore, character must be formed in order to prepare students as a generation of hope for the nation and the successor of development in order to have a strong and correct attitude and mindset in the effort to build a nation and himself. Phenomenon shows that students are still weak in character, especially at the elementary school level, so they need serious attention and handling in order to get a comprehensive and systematic problem solving. This is important because the position of the primary school is the first and main gate in laying the foundations of character or morals based on the concept of positive moral values in order to prepare graduates to become whole individuals.